THE IMPACT OF CAR, NPF, AND FDR ON ROE OF ISLAMIC COMMERCIAL BANKS LISTED ON IDX FOR THE PERIOD 2024–2025 - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2026)
Islamic banking continues to face various challenges in enhancing its competitiveness relative to conventional banking. This can be achieved by improving service quality and achieving sustainable operational performance. This study aims to analyze the impact of CAR, NPF, and FDR on ROE, both partially and simultaneously, in Islamic commercial banks listed on the IDX during the 2024–2025 period. The variables analyzed include CAR, NPF, and FDR as independent variables, while ROE serves as the dependent variable. For data analysis, simple and multiple regression were used with the assistance of SPSS version 26 software. The results indicate that, individually, CAR has a significant impact on the ROE of Islamic commercial banks during the study period. On the other hand, NPF and FDR do not show a significant impact on ROE. However, simultaneous analysis indicates that these three independent variables collectively have a significant influence on the ROE of Islamic commercial banks listed on the IDX for the 2024–2025 period.